Information Exchange in Group Decision Making: The Hidden Profile Problem Reconsidered - Lightle, John P.; Kagel, John H.; Arkes, Hal R. (Management Science, 2009)
Group decision making provides a mechanism for channeling individual members' knowledge into productive organizational outcomes. However, in hidden profile experiments in which group members have common information favoring an inferior choice, with private information favoring a superior choice, groups typically choose an inferior alternative. We report a hidden profile experiment where we induce homogenous preferences over choice characteristics and provide financial incentives so that the common purpose assumptions of the model hold more completely than in past experiments. Nevertheless, groups continue to choose an inferior alternative most of the time. These failures primarily result from mistakes in recalling information. Mistakes in recalling common information (which favors an inferior candidate) are typically corrected, whereas mistakes in recalling the private information needed to uncover the hidden profile cannot be corrected. Therefore, the dismal performance of groups in pooling the information needed to identify the superior option primarily result from the structure of the problem rather than deficiencies in how groups share and process information. The discussions necessary to resolve mistakes in recalling common information also help to explain the often noted fact that groups spend a disproportionate amount of time discussing common information.